Energy justice : US and international perspectives - Salter, Raya; Gonzalez, Carmen G., 1962-; Kronk Warner, Elizabeth Ann; Bullard, Robert D. 1946- (New horizons in environmental and energy law, 2018)
Energy Justice: US and International Perspectives is a pioneering analysis of energy law and policy through the framework of energy justice. While climate change has triggered unprecedented investment in renewable energy, the concept of energy justice and its practical application to energy law and policy remain under-theorized. This volume breaks new ground by examining a range of energy justice regulatory challenges from the perspective of international law, US law, and foreign domestic law. The book illuminates the theory of energy justice while emphasizing practical solutions that hasten the transition from fossil fuels and address the inequities that plague energy systems. Among the first edited volumes to focus wholly on the emerging field of energy justice, this book takes a multidisciplinary approach that examines energy law and policy through the lens of environmental justice, climate justice, indigenous rights, human rights, and energy democracy. Contributions from prominent scholars and practitioners demonstrate how energy justice frameworks can be applied in theory and practice. With a foreword by Dr Robert Bullard, Energy Justice is a critical resource for: law students and professors; researchers, students and faculty of graduate and undergraduate courses in the area of energy and the environment; and advocates and policymakers in the area of energy and the environment.